2020
DOI: 10.1186/s12920-020-00831-9
|View full text |Cite
|
Sign up to set email alerts
|

The first familial NSD2 cases with a novel variant in a Chinese father and daughter with atypical WHS facial features and a 7.5-year follow-up of growth hormone therapy

Abstract: Background Wolf-Hirschhorn syndrome is a well-characterized genomic disorder caused by 4p16.3 deletions. Wolf-Hirschhorn syndrome patients exhibit characteristic facial dysmorphism, growth retardation, developmental delay, intellectual disability and seizure disorders. Recently, NSD2 gene located within the 165 kb Wolf-Hirschhorn syndrome critical region was identified as the key causal gene responsible for most if not all phenotypes of Wolf-Hirschhorn syndrome. So far, eight NSD2 loss of function variants hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…A comparison of our patient's features and the genetic result with the literature describing cases that only affect NSD2 (WHSC1) indicated that variants and deletions that only affect NSD2 manifest as mild WHS phenocopies (see Zanoni et al 1 describing 18 original patients, 13 previously published patients, [3][4][5][6][7][8][9] and the patient of our work).…”
supporting
confidence: 54%
See 1 more Smart Citation
“…A comparison of our patient's features and the genetic result with the literature describing cases that only affect NSD2 (WHSC1) indicated that variants and deletions that only affect NSD2 manifest as mild WHS phenocopies (see Zanoni et al 1 describing 18 original patients, 13 previously published patients, [3][4][5][6][7][8][9] and the patient of our work).…”
supporting
confidence: 54%
“…Interestingly, his father carrying the same NSD2 variant showed mild intellectual disability presenting a seizure after a fever episode as a child, during which encephalitis was suspected, but no definite diagnosis was made. 9 Because of the very low frequency of seizures in NSD2related disorders in comparison with WHS, several genes included in the deleted region have been described as candidates. LETM1 has been considered as one of the candidates, but some patients with deletions in LETM1 do not present seizures.…”
mentioning
confidence: 99%
“…Hence, the clinical spectrum of NSD2 deletion encompasses: prenatal and postnatal growth restriction [ 14 ], microcephaly, developmental delay [ 15 ], congenital heart defects and several phenotypic traits, including hypertelorism, upward-slanting palpebral fissures, prominent nasal bridge, abnormal teething and micrognathia. Cleft palate has been described in fourteen patients [ 16 – 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The WHS core phenotype (pre and postnatal growth delay, distinctive craniofacial features, intellectual disability, and seizures) is due to haploinsufficiency of several closely linked genes as opposed to a single gene (Battaglia, 2021;Maas et al, 2008;Zollino et al, 2008). This view is now clearly supported by the recognition of a number of individuals carrying a pathogenic variant of WHSC1 (NSD2) (loss of function, missense, truncating), or CTBP1, showing much of the core phenotype of the syndrome (developmental delay and failure to thrive; or intellectual disability and subtle dysmorphic features; or prenatal growth delay and intellectual disability) (Beck et al, 2016;Boczek et al, 2018;Derar et al, 2019;Hu et al, 2020;Jiang et al, 2019;Lozier et al, 2018) (Figures 5 and 6). The observation of such individuals has become possible with the wider employment of ES in the genetic testing of persons with neurodevelopmental disorders.…”
Section: Clinical Exome Sequencing Periodmentioning
confidence: 99%